Algorithm-enhanced English grammar learning: A structured module development approach - Shofiyuddin, Muh; Sutama; Prayitno, Harun Joko (Indonesian Journal of Applied Linguistics, 2025)
Grammar is an essential competence for effective communication, yet many students have difficulties understanding and mastering it. This study aims to develop a comprehensive learning module integrating algorithm principles with English grammar to enhance students' grasp of English structure by following a systematic approach encompassing Analysis, Design, Development, Implementation, and Evaluation (ADDIE). However, it focused primarily on implementation and evaluation phases. The novelty lies in the implementation of the algorithm principle used to enhance students’ grammar mastery. In this case, English structures are learned through automatic patterns to make them easier to master. Participants included students from the English Education Department at three different universities in Central Java with diverse educational backgrounds, while the product was implemented (limited test) at one of them. A thorough needs analysis revealed that students found that grammar learning was complex and challenging, necessitating simpler, more engaging instructional methods. In response, a targeted product was developed based on these insights. The validation indicated a positive reception of the module, with 66% as "Good," 17% as "Average," and 16% as "Very Good," with no evaluation falling into "Poor" or "Unsatisfactory" categories. These findings suggest that the module is a viable tool for enhancing grammar instruction. Besides, the implementation gained a p-value of 0.004 that meant having significance in using the module. The study not only contributes to the pedagogical framework for teaching English grammar but also highlights the importance of innovative approaches in language education. Further research could explore the long-term impacts of such modules in various learning contexts.